Cover Picture: Programming DNA Nanoassembly for Enhanced Photodynamic Therapy (Angew. Chem. Int. Ed. 5/2020). Issue 5 (13th December 2019) - Pan, Min; Jiang, Qunying; Sun, Junlin; Xu, Zhen; Zhou, Yizhuo; Zhang, Li; Liu, Xiaoqing
Abstract : Designer DNA nanosponges can enhance the efficacy of photodynamic therapy by relieving hypoxia‐associated resistance, as reported by X. Liu et al. in their Research Article on page 1897. The programmable DNA assembly provides a safe and effective approach for in vitro and in vivo cancer treatment.